Behaviours and experiences of nurses during the COVID‐19 pandemic in Turkey: A mixed methods study. (31st August 2021) - Cengiz, Zeliha; Isik, Kevser; Gurdap, Züleyha; Yayan, Emriye Hilal
Abstract: Aim: The aim of this work is to present behaviours and experiences of nurses in Turkey during the current coronavirus pandemic. Background: The coronavirus pandemic leads to difficulties for most health care workers, especially for nurses who mostly accompany patients and are on the front line. Methods: In the study, a parallel mixed pattern converging quantitative and qualitative research methods was used. Results: The model revealed that 41 years old or older, diabetic, female, single professionals, working in the pandemic department took more personal measures. Five main themes appeared regarding the experiences of the nurses during the pandemic period: (1) psychological and mental strain; (2) personal protective equipment; (3) organizational, physical, and social strains; (4) change in professional values; (5) turning the crisis into an opportunity. Conclusions: Personal measures are associated with the risk status. There is a need to protect nurses with significant measures by providing psychosocial support, meeting their basic needs, and preventing all complications likely to occur due to increasing workload. Implications for Nursing Management: More efforts should be made to ensure good work, fair treatment, no tolerance for discrimination, and equal compensation conditions.